1993
DOI: 10.1055/s-2007-1006657
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Reconstruction in Limb-Salvage Procedures: Comparison between Primary and Secondary Reconstruction

Abstract: Limb-salvaging procedures after malignant tumor resection in the extremities were performed in 22 cases, utilizing microsurgical tissue transplantation. Five patients had soft-tissue tumors and 17 had bone tumors. Thirteen cases were primarily and nine were secondarily reconstructed. The advantages and disadvantages of both primary and secondary reconstructions were compared: as to technical difficulty, primary reconstruction was much easier. Chemotherapy was necessary just before and/or after reconstruction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This finding was supported by a recent study of the effects of cisplatin on the incorporation of fresh syngeneic and frozen allogeneic cortical bone grafts in another rat model (Zart et al 1993), which showed that the total bone incorporation in chemotherapy-treated rats was less than in those which did not receive chemotherapy. While these 2 studies were confirmed by a report in humans (Usui et al 1993), that report found that eventual union occurred in all cases after further conventional bone grafts. In contrast, Aho et al (1994) and Wang (1 993) concluded that adjuvant chemotherapy had no major effect on the union rate of host-allograft bone.…”
Section: Discussionmentioning
confidence: 53%
“…This finding was supported by a recent study of the effects of cisplatin on the incorporation of fresh syngeneic and frozen allogeneic cortical bone grafts in another rat model (Zart et al 1993), which showed that the total bone incorporation in chemotherapy-treated rats was less than in those which did not receive chemotherapy. While these 2 studies were confirmed by a report in humans (Usui et al 1993), that report found that eventual union occurred in all cases after further conventional bone grafts. In contrast, Aho et al (1994) and Wang (1 993) concluded that adjuvant chemotherapy had no major effect on the union rate of host-allograft bone.…”
Section: Discussionmentioning
confidence: 53%
“…The cause in Case 4 appeared to be the ill effects of chemotherapy. 10 The causes of non-union in Case 5 appeared to be a small gap between the radius and grafted fibula and inadequate internal fixation due to the choice of too small a plate (see Fig. 3B).…”
Section: Discussionmentioning
confidence: 94%
“…Vascularized autografts demand technical expertise and infrastructure which may be limited in many centres. 17 Allografts and recycled bone are also fraught with chances of infection, fracture, delayed incorporation, need for prolonged immobilisation and cannot be considered as definite options. Fresh frozen allografts are sparingly available and in addition carry risk of transmission of viral illnesses and immunological rejection.…”
Section: Discussionmentioning
confidence: 99%